Óscar Pérez (1981-2018): chronicle of a death foretold - Deneuville, Allan (2020)
In this article, we propose the comparative study of two works that use videos of Venezuelan political opponent Óscar Pérez who was killed during a military raid. Romain Champalaune’s film (The Life and Death of Óscar Pérez) and the website of the British collective Forensic Architecture question us about the future of user-generated content and the place of the artist and the researcher in the society of hyper-production of texts and documents. After introducing the Perez case and presenting the works, we analyze the regime of proof and the idea of truth and the archive in the era of algorithmic governmentalities. Finally, we study how investigation and the collection of user-generated content allow for a shift in our power regimes through the implementation of counter-narration to that of the powers that be.